Mechanism of EPFRs formation from hydroquinone on transition metal oxide surfaces: coupled experimental and density functional theory study - Junyao Fu; Lingqin Zhao; Aijia Zhang; Guohao Yang; Fan Yu; Yanjun Hu (Waste Disposal & Sustainable Energy, 2026)

Activated carbon-quartz sand dual-layer filter material accelerates the start-up of filter: Performance and mechanism - Sen Yang; Dong Li; Hongpeng Li; Jifang Zheng; Yanjun Zhu; Sibo Fu; Huiping Zeng; Jie Zhang (Journal of Water Process Engineering, 2026)

A synergistic metal ion–silane strategy enables fire-safe, water-repellent, and mold-resistant flattened bamboo board - Longchao Ma; Genmiao Wan; Yan Wang; Chenkai Dou; Danhe Liu; Yue Jiao; Hao Sun; Xinzhou Wang; Yi Chen; Qiliang Fu; Yanjun Li (Chemical Engineering Journal, 2026)

CircGABRB2_006 Drives Malignant Progression and EMT in Papillary Thyroid Carcinoma via the miR-296-5p/FGFR1 Axis - Chuan Wan; Yanjun Guo; Han Guo; Jingjing Zhu; Fangchao Liu; Yunyuan Zhang; Bingfei Cheng; Juanjuan Li; Ying Xin; Bingzi Dong; Weiwei Fu; Dongmei Meng; et al. (Biochemical Genetics, 2026)

A few-shot fault diagnosis method for ship motors based on multi-source data and multi-view task guidance - Yuan Xu; Deqiang He; Chunyang Dai; Zhenzhen Jin; Yanjun Chen; Yang Fu (Ocean Engineering, 2026)

Synergistic effect of cocatalyst engineering and radical regulation toward high selectivity in one-step methane conversion - Chuan Yu; Mingli Fu; Keke Tang; Yanjun Li; Lei Liu; Chen Yang; Daiqi Ye (Journal of Environmental Chemical Engineering, 2026)

Multi-level metabolic engineering for efficient ergothioneine production in yeast using a Pleurotus ostreatus-derived pathway - Zhongjuan Di; Yanjun Huo; Yuejun Fu; Bo Li; Yingping Zhuang (Chemical Engineering Journal, 2026)

Strong tri-genic epistasis among natural alleles of the OsMYB2–OsGH18–OsCAD3 module enhances drought tolerance in rice - Mingyue Huo; Shanwen Wang; Fan Zhang; Min Li; Ming Yin; Yuxin Lei; Yanfang Wang; Yanjun Chen; Dapu Liu; Xiuqin Zhao; Binying Fu; Fengyi Hu; et al. (Molecular Plant, 2026)

Construction of CuO-ZnO interface electron channels accelerates the methane partial oxidation for high formaldehyde production - Yanjun Li; Chuan Yu; Chen Yang; Keke Tang; Xueyun Zhong; Sijia Weng; Chuying Qiu; Mingli Fu; Daiqi Ye (Journal of Environmental Chemical Engineering, 2026)

Low-temperature anammox efficiency is governed by matrix-mediated modulation of quorum sensing - Yanjun Zhu; Dong Li; Sen Yang; Sibo Fu; Hongpeng Li; Songyue Li; Huiping Zeng; Jie Zhang (Bioresource Technology, 2026)

Sediment sink-source shifts drive intensified internal phosphorus (P) release during the rainy season in a eutrophic plateau lake - Chaoran Guo; Fu Zhang; Yanjun Wu; Chengfei Tong; Yuyi Wang; Jianxia Cai; Zheng Zhao; Jinliang Liu; Qi Yang; Xiaozhi Gu; Jicheng Zhong; Jizheng Pan (Water Research, 2026)

Quantifying nitrate dynamics in deep vadose zone under irrigated farmland in the North China Plain: Insights from continuous in-situ monitoring - Hanbing Jiang; Di Geng; Jiawei Fu; Meiying Liu; Yongqing Qi; Leilei Min; Shiqin Wang; Yanjun Shen (Agriculture, Ecosystems & Environment, 2026)

Mussel-inspired coating anchored polyquaternium functionalized nonwoven fabrics for microplastic adsorption - Yuanshuai Wan; Yanjun Jia; Yonggui Guo; Jianteng Sun; Maofeng Liang; Lichao Gao; Haidong Cao; Tiantian Liu; Hongxiang Zhao; Yuliang Pang; Yanwei Fu; Yu Zhao; et al. (Journal of Environmental Chemical Engineering, 2025)

Activating graphitic carbon via a core/shell WO3/carbon architecture for electrocatalytic deactivation of dilute antibiotics - Wenyang Fu; Yanjun Yin; Jiahong Zou; Chunyang Dan; Shenbin Zheng; Huimin Sui; Yinan Liu; Yan Zou; Heng Shi; Guangming Jiang (Chemical Engineering Journal, 2025)

Impact of Built Environment on Urban Vitality in Shrinking Cities: Moderating Effect of Housing Vacancy - Hui Fu; Guolei Zhou; Hongri Sun; Yu Jin; Hanchun Wu; Yanjun Liu (Chinese Geographical Science, 2025)

Multi-component heterogeneous interface engineering and magnetic domain evolution for broadband electromagnetic wave attenuation - Yuhui Peng; Jiarong Liu; Zhaobo Feng; Jinbin Peng; Yangxiao Guo; Yue Zhang; Yanjun Fu; Chongbo Liu; Lianwen Deng (Chemical Engineering Journal, 2025)

Enhanced denitrification and fouling control in hydrogen-based membrane biofilm reactor using novel flat membrane module - Mingyi Lu; Quan Feng; Fan Qin; Yanjun Wu; Haoran Duan; Shanfei Fu; Rongbo Guo (Bioresource Technology, 2025)

WB-assisted activation of periodate by Fe(III) for decontamination: Periodate concentration-dependent mechanistic shift - Yulu Xu; Yu Mei; Yanjun Li; Chenye Fu; Yuantai Li; Yuheng Zhong; Junxi Song; Gang Yang; Shihuai Deng; Xiaohui Lu; Jiali Peng; Bo Lai (Journal of Hazardous Materials, 2025)

Nitrilotriacetic acid-assisted activation of periodate by Fe(III) for organic pollutant degradation: the critical roles of high-valent iron species formation and coordination inhibition by phenolic contaminants - Xiaohui Lu; Yuantai Li; Shihuai Deng; Yanjun Li; Chenye Fu; Guochun Lv; Da Wang; Junxi Song; Hong Xiao; Jiali Peng; Bo Lai (Chemical Engineering Journal, 2025)

Sunlight-driven hydrogen peroxide activation via copper hydroxyphosphate with broad spectrum response for imidacloprid degradation: Mechanism insight and DFT calculation - Haoran Zhang; Jiang Li; Yujiao Liu; Sihao Fu; Tianjie Su; Lingyu Meng; Yunfei Wang; Nian Ma; Guocheng Liu; Qinghua Yan; Yanjun Xin; Shuaishuai Xin (Chemical Engineering Journal, 2025)

Effect of Attribute Information of Recycled Water on Willingness to Accept: Evidence from an Event-Related Potential (ERP) Experiment - Hanliang Fu; Bo Dong; Zhifang Wu; Caixia Hou; Yanjun Ren (Water Resources Management, 2025)

Identifying omitted high reactive VOCs emission sources in China based on new speciated emission inventory - Di Wang; Jinhong Du; Li Yang; Jinmin Zhao; Xinmin Zhang; Zhihao Zhang; Wenjuan Zhao; Weiqi Zhang; Yuzhe Zhang; Jinghua Ma; Wenjing Jin; Yanjun Ren; et al. (Journal of Cleaner Production, 2025)

Shelter efficiency of windbreak influenced by stand configuration - Ruijie Zhang; Rui Ma; Yanjun Ma; Fu Zhang; Linyuan Wei; Gazangzhuoma Xie (Biosystems Engineering, 2025)

Optimal design of marine nuclear power deaerator based on improved particle swarm optimization algorithm - Jiarui Zhao; Yanjun Li; Xu Chen; Yuan Fu; Baozhi Sun; Yuanwei Cao; Jianxin Shi (Annals of Nuclear Energy, 2025)

Decoding the effect of antibiotics on biofilm formation in biofilters - Sen Yang; Dong Li; Sibo Fu; Jifang Zheng; Yanjun Zhu; Hongpeng Li; Huiping Zeng; Jie Zhang (Journal of Environmental Management, 2025)

Tectonic setting, paleoenvironment and REE source of the Lower Cambrian phosphorites, Yangtze Block (South China) - Chuan Guo; Yong Fu; Peng Xia; Zhen Yang; Yanjun Li; Zhongfei Pan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Exploring the interaction between quorum sensing and sludge physical properties in Anammox systems - Yanjun Zhu; Dong Li; Sibo Fu; Hongpeng Li; Sen Yang; Songyue Li; Yuliang Zhu; Huiping Zeng; Jie Zhang (Bioresource Technology, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Electrocatalytic conversion of nitrate to ammonia on the oxygen vacancy engineering of zinc oxide for nitrogen recovery from nitrate-polluted surface water - Wenyang Fu; Yanjun Yin; Shuxian He; Xiangyi Tang; Yinan Liu; Fei Shen; Yan Zou; Guangming Jiang (Environmental Research, 2025)

Adaptation mechanisms and efficiency of anammox bacterial aggregates in various reactor systems during the start-up period - Yanjun Zhu; Dong Li; Sibo Fu; Hongpeng Li; Sen Yang; Jifang Zheng; Huiping Zeng; Jie Zhang (Journal of Water Process Engineering, 2024)

Towards a high-rate operation of contact stabilization process: A microscopic view of carbon capture properties - Sibo Fu; Dong Li; Kunming Fu; Xiaohang Zhang; Yanjun Zhu; Sen Yang; Huiping Zeng; Jie Zhang (Environmental Research, 2024)

Balance of heat management and salt-resistance on solar interfacial evaporator actively adjusted by the electric field with periodically changed direction - Shijin Fu; Ziqi He; Yuzhao Ma; Xiuliang Liu; Deqiang He; Yanjun Chen (Desalination, 2024)

Towards a high-rate operation of contact stabilization process: Challenges of flocculation and floc stability - Sibo Fu; Dong Li; Kunming Fu; Yanjun Zhu; Sen Yang; Xiaohang Zhang; Jie Zhang (Journal of Environmental Management, 2024)

Cobalt single-site molecular Catalyst-mediated electrochemical Hydrodechlorination for detoxification of halogenated Antibiotics: Performance, reaction pathway and mechanism - Yinan Liu; Xiangyi Tang; Fei Shen; Jiahong Zou; Yanjun Yin; Zhaojie Jiao; Xiaoshu Lv; Wenyang Fu; Yan Zou; Guangming Jiang; Hong Liu (Chemical Engineering Journal, 2024)

New insight into catalytic performance and reaction mechanism for butyl acetate over CeO2 catalysts: Oxygen vacancy and surface reactive oxygen species - Jiajia Lin; Wenjing Kong; Chuying Qiu; Xueyun Zhong; Yanjun Li; Mingli Fu; Zhenguo Li (Journal of Environmental Chemical Engineering, 2024)

Does risk preference matter to consumers’ willingness to pay for functional food: Evidence from lab experiments using the eye-tracking technology - Shihang Zhen; Xianli Xia; Luchen Huang; Yihan Cao; Hanliang Fu; Yanjun Ren (Food Quality and Preference, 2024)

Parametric study of correlation of mainshock-aftershock ground motions based on Copula theory - Ziyan Wang; Xiaojun Li; Su Chen; Lei Fu; Bin Zhang; Xianwei Liu; Yanjun Zhu (Journal of Seismology, 2024)

Regrowth or smart decline? A policy response to shrinking cities based on a resilience perspective - Yu Jin; Guolei Zhou; Hongri Sun; Hui Fu; Hanchun Wu; Yanjun Liu (Sustainable Cities and Society, 2024)

In vitro and in vivo activity of ceftazidime/avibactam and aztreonam alone or in combination against mcr-9, serine- and metallo-β-lactamases–co-producing carbapenem-resistant Enterobacter cloacae complex - Wengang Li; Jisheng Zhang; Yanjun Fu; Jianmin Wang; Longjin Liu; Wenzhang Long; Kaixin Yu; Xinhui Li; Chunli Wei; Xushan Liang; Jin Wang; Chunjiang Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Unprecedented recent warming as recorded by tree-ring in the western Qinling Mountains, China - Yiyun Yuan; Yang Deng; Linlin Gao; Xiyue Fu; Yanjun Xu; Xiaohua Gou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

A new method for generating equidistant/equiratio line between two points on the earth ellipsoid - Jianhui Zhang; Ruiquan Fu; Yanjun Cui; Shaoyang Chen; Mingjie Li; Xuefeng Zhang (Computers & Geosciences, 2024)

Mn–Co–Ce/biochar based particles electrodes for removal of COD from coking wastewater by 3D/HEFL system: Characteristics, optimization, and mechanism - Qiaoyun Zhu; Xueling Liu; Xiaorong Xu; Xiaoyu Dong; Jingjing Xiang; Benquan Fu; Yanjun Huang; Yi Wang; Guozhi Fan; Lei Zhang (Environmental Research, 2024)

Stability analysis of unsaturated soil slopes with cracks under rainfall infiltration conditions - Lei Zhang; Xin Jiang; Rong Sun; Hanyan Gu; Yongguo Fu; Yanjun Qiu (Computers and Geotechnics, 2024)

Solar-driven biomass chemical looping gasification using Fe3O4 for syngas and high-purity hydrogen production - Dequan Xu; Bo Wang; Xian Li; Yoke Wang Cheng; Wenming Fu; Yanjun Dai; Chi-Hwa Wang (Chemical Engineering Journal, 2024)

Exploring recharge mechanisms of soil water in the thick unsaturated zone using water isotopes in the North China Plain - Huawu Wu; Fan Song; Leilei Min; Jing Li; Yanjun Shen; Yanan Huang; Hongxiang Fan; Jinzhao Liu; Congsheng Fu (CATENA, 2024)

Progression of an emission inventory of China integrating CO2 with air pollutants: A chance to learn the influence of development on emissions - Guorui Zhi; Jinhong Du; Aizhong Chen; Wenjing Jin; Na Ying; Zhihui Huang; Peng Xu; Di Wang; Jinghua Ma; Yuzhe Zhang; Jiabao Qu; Hao Zhang; et al. (Atmospheric Environment, 2024)

Housing vacancy identification in shrinking cities based on multi-source data: A case study of Fushun city in Northeast China - Hongri Sun; Guolei Zhou; Yanjun Liu; Hui Fu; Yu Jin (Journal of Geographical Sciences, 2024)

Flame retardant and multifunctional BC/MXene/MSiCnw/FRTPU aerogel composites with superior electromagnetic interference shielding via “Consolidating” method - Hengrui Wang; Kexin Chen; Yongqian Shi; Yanjun Zhu; Songqiong Jiang; Yan Liu; Shijie Wu; Chenxin Nie; Libi Fu; Yuezhan Feng; Pingan Song (Chemical Engineering Journal, 2023)

Unraveling roles of the intermediate settler in a microaerobic hydrolysis sludge in situ reduction process - Zhen Zhou; Yiyue Sun; Li Fu; Yi Zuo; Yanjun Shao; Lihua Wang; Chuanting Zhou; Ying An (Bioresource Technology, 2023)

Essential role of atomic H* in activating hydrogen peroxide to produce singlet oxygen for emerging organic contaminants degradation - Xixi Chen; Wanyi Fu; Yulong Yang; Yanjun Li; Kai Yang; Xuanbo Xu; Xihui Zhang (Journal of Environmental Chemical Engineering, 2023)

Enhanced H2O2 utilization efficiency in Fenton-like system for degradation of emerging contaminants: Oxygen vacancy-mediated activation of O2 - Xixi Chen; Wanyi Fu; Zhichao Yang; Yulong Yang; Yanjun Li; Hui Huang; Xihui Zhang; Bingcai Pan (Water Research, 2023)

Advancing the bioconversion process of food waste into methane: A systematic review - Endashaw Workie; Vinor Kumar; Amit Bhatnagar; Yiliang He; Yanjun Dai; Yen Wah Tong; Yinghong Peng; Jingxin Zhang; Cunbin Fu (Waste Management, 2023)

Achieving highly efficient pH-universal hydrogen evolution by Mott-Schottky heterojunction of Co2P/Co4N - Mingliang Qin; Lanli Chen; Huaming Zhang; Muhammad Humayun; Yanjun Fu; Xuefei Xu; Xinying Xue; Chundong Wang (Chemical Engineering Journal, 2023)

The Critical Factors and Preventive Measures of Impoundment of Tailings Using Active Surface Subsidence Zones - Yang Liu; Yanjun Zhou; Rongxing He; Jianli Cao; Fengyu Ren; Fu Yu; Lu Yue (Geotechnical and Geological Engineering, 2023)

Circular RNA circPBX3 promotes cisplatin resistance of ovarian cancer cells via interacting with IGF2BP2 to stabilize ATP7A mRNA expression - Lihua Fu; Dan Zhang; Nuo Yi; Yanjun Cao; Yaxian Wei; Wenjing Wang; Li Li (Human Cell, 2022)

Matching of Residential and Commercial Space in Shrinking Cities from the Perspective of Supply and Demand: A Case Study of Yichun City, China - Yining Zhang; Guolei Zhou; Yanjun Liu; Hui Fu; Hongri Sun (Chinese Geographical Science, 2022)

CircLPAR3 Acts as an Oncogene in Oral Squamous Cell Carcinoma Through Regulating the miR-643/HMGB2 Network - Yunxia Fu; Chunyan Qiu; Yanjun Yang; Jianying Lu; Yun Qi (Biochemical Genetics, 2022)

Black-Box Modelling and Prediction of Deep-Sea Landing Vehicles Based on Optimised Support Vector Regression - Hongming Sun; Wei Guo; Yanjun Lan; Zhenzhuo Wei; Sen Gao; Yu Sun; Yifan Fu (Journal of Marine Science and Engineering, 2022)
Due to the nonlinearity of the deep-seafloor and complexity of the hydrodynamic force of novel structure platforms, realising an accurate motion mechanism modelling of a deep-sea landing vehicle (DSLV) is difficult. The support vector regression (SVR) model optimised through particle swarm optimisation (PSO) was used to complete the black-box motion modelling and vehicle prediction. In this study, first, the prototype and system composition of the DSLV were proposed, and subsequently, the high-dimensional nonlinear mapping relationship between the motion state and the driving forces was constructed using the SVR of radial basis function. The high-precision model parameter combination was obtained using PSO, and, subsequently, the black-box modelling and prediction of the vehicle were realised. Finally, the effectiveness of the method was verified through multi-body dynamics simulation and scaled test prototype data. The experimental results confirmed that the proposed PSO–SVR model could establish an accurate motion model of the vehicle, and provided a high-precision motion state prediction. Furthermore, with less calculation, the proposed method can reliably apply the model prediction results to the intelligent behaviour control and planning of the vehicle, accelerate the development progress of the prototype, and minimise the economic cost of the research and development process.

Identifying the sources of seasonal predictability based on climate memory analysis and variance decomposition - Da Nian; Naiming Yuan; Kairan Ying; Ge Liu; Zuntao Fu; Yanjun Qi; Christian L. E. Franzke (Climate Dynamics, 2020)

Spatial Pattern of Female Non-agricultural Employment and Its Driving Forces in Guangdong Province, China: A Perspective of Individual and Family-level - Zhanhui Fu; Lin Mei; Yanjun Liu; Junfeng Tian; Rumin Zheng; Jing Tian (Chinese Geographical Science, 2020)

Influential intensity of urban agglomeration on evolution of eco-environmental pressure: a case study of Changchun, China - Yanjun Liu; Jing Zhang; Chenggu Li; Guolei Zhou; Zhanhui Fu; Degang Liu (Chinese Geographical Science, 2017)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Altitude variation in chilling tolerance among natural populations of Elymus nutans in the Tibetan Plateau - Juanjuan Fu; Yuefei Xu; Yanjun Miao; Tianming Hu (Acta Physiologiae Plantarum, 2016)

The response and detoxification strategies of three freshwater phytoplankton species, Aphanizomenon flos-aquae, Pediastrum simplex, and Synedra acus, to cadmium - Xiaofei Ran; Hong Yue; Xiaoli Fu; Yuanhao Kang; Sha Xu; Yanjun Yang; Jinzhu Xu; Junqiong Shi; Zhongxing Wu (Environmental Science and Pollution Research, 2015)

Comparative genomic approach reveals novel conserved microRNAs in Inner Mongolia cashmere goat skin and longissimus dorsi - Rui Su; Shaoyin Fu; Yanjun Zhang; Ruijun Wang; Yanhong Zhou; Jinquan Li; Wenguang Zhang (Molecular Biology Reports, 2015)

siRNA Combinations Mediate Greater Suppression of Hepatitis B virus Replication in Mice - Guiqiu Li; Lu Fu; Jinghong Jiang; Yuzhuo Ping; Yanjun Huang; Yongchen Wang (Cell Biochemistry and Biophysics, 2014)

New eolian red clay sequence on the western Chinese Loess Plateau linked to onset of Asian desertification about 25 Ma ago - Xiaoke Qiang; Zhisheng An; Yougui Song; Hong Chang; Youbin Sun; Weiguo Liu; Hong Ao; Jibao Dong; Chaofeng Fu; Feng Wu; Fengyan Lu; Yanjun Cai; et al. (Science China Earth Sciences, 2011)

Characterization of Anthocyanidin Synthase (ANS) Gene and anthocyanidin in rare medicinal plant-Saussurea medusa - Liqin Cheng; Yanjun Xu; Erich Grotewold; Zhiping Jin; Fengyan Wu; Chunxiang Fu; Dexiu Zhao (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)